Die Unfähigkeit, sich zu erkennen : Sophokles' Tragödien - Lefèvre, Eckard. (Mnemosyne, Supplements, 2001)
This book interprets all seven Sophoclean tragedies (5th century B.C.) as a whole, focussing on the aspect of individuals being guilty of not reaching proper conclusions about their own selves and their situation, although they possess the means and ability to do so. Chapter I offers exact definitions of the concepts employed in analyzing the tragedies. Chapters II-VIII each contain a detailed interpretation of one of Sophocles' seven tragedies. Chapter IX ('Tableau') presents the dramatic works within the context of Greek history of thought and politics of their time, while Chapter X sheds some light on how Sophoclean concepts were continued in the comedies of Menander. This study should not only prove helpful to scholars in the field of literary studies, but also to historians, philosophers and all those interested in history of thought and cultural history, since it examines in a fundamental way the thought of one of the most important poets of ancient Europe.